Colorectal infiltrating deep endometriosis: Laparoscopic treatment. A case report - Di Buono, Giuseppe; Micheli, Matilde; Russo, Gaia; Vella, Roberta; Amato, Giuseppe; Geraci, Girolamo; Agrusa, Antonino (Frontiers in Surgery, 2022)
Endometriosis is a disease affecting about 10% of women in fertile age. A particular presentation is deep infiltrating endometriosis of the rectosigmoid colon with symptoms that can mimic an intestinal obstruction or neoplasm. We report the case of a 39-year-old woman with pelvic pain during the menstrual cycle and significant anemia who presented an ectopic endometrial tissue in correspondence of the rectum. Because of the thickness of the lesion the patient underwent a segmental laparoscopic colorectal resection with end-to-end anastomosis.